Freeze Granulated Zeolites X and A for Biogas Upgrading - Narang, Kritika (Molecules, 2020)
Biogas is a potential renewable energy resource that can reduce the current energy dependency on fossil fuels. The major limitation of utilizing biogas fully in the various applications is the presence of a significant volume fraction of carbon dioxide in biogas. Here, we used adsorption-driven CO(2) separation using the most prominent adsorbents, NaX (faujasite) and CaA (Linde Type A) zeolites. The NaX and CaA zeolites were structured into hierarchically porous granules using a low-cost freeze granulation technique to achieve better mass transfer kinetics. The freeze granulation processing parameters and the rheological properties of suspensions were optimized to obtain homogenous granules of NaX and CaA zeolites 2–3 mm in diameter with macroporosity of 77.9% and 68.6%, respectively. The NaX and CaA granules kept their individual morphologies, crystallinities with a CO(2) uptake of 5.8 mmol/g and 4 mmol/g, respectively. The CO(2) separation performance and the kinetic behavior were estimated by breakthrough experiments, where the NaX zeolite showed a 16% higher CO(2) uptake rate than CaA granules with a high mass transfer coefficient, 1.3 m/s, compared to commercial granules, suggesting that freeze-granulated zeolites could be used to improve adsorption kinetics and reduce cycle time for biogas upgrading in the adsorption swing technology.